(3JMSjf LhOI GdUjGfI ai Gdfbd (B: s (3OQGSI MGdI (B/ s - (3MSGe UdGM MGaXs; (3MLGRi RGgQ (B: s ((3GdbGgQI (B: s (3MSGe UdGM MGaX (B: s, 2019)
(3ai gPg GdOQGSI ehVhY GdHMK Je GdJWHjb HTcd Yedi Ydj GMO GdfeGPL GdNGUI HehVhY GdOQGSI h gi JeKd TQcI ef GdTQcGJ GdJGHYI ddfbd GdeUQi h HOQGSI CSGS GdeTcdI GdJi jYGfi efgG bWGY GdUjGfI HJdc GdTQcI JHjf Ef ddeTcdI CSHGH eNJdaI efgG(B. (3GdJcQGQ GdeSJeQ ddCYWGd Ydi eSJhi GdhMOGJ fJjLI VYa YedjGJ GdUjGfI(B. (3RjGOI GdgOQ ai bWY ZjGQ GdhMOGJ fJjLI ShA YedjGJ GdUjGfI(B. (3YOe EJHGY GdCSGdjH GdYdejI h HQGeL GdUjGfI GdeJbOeI eeG jDKQ HTcd SdHj Ydi GdYfUQ GdHTQi h GdYfUQ GdRefi h RjGOI GdJcdaI(B. (3h ddJCcO dMOhK Jdc GdeTcdI fe GdJYGed eY GdHjGfGJ HYO LeYgG HGSJNOGe GdMRe GdEMUGFjI dHQfGeL (B((3ES Hi ES ES(B) (3h PGdc dYed GNJHGQGJ GdaQhb h GdfSH ddJCcO ef MOhK GdeTcdI h Je CjVG GSJNOGe GdCSGdjH GdEMUGFjI GdeNJdaI efgG (B((3GdeJhSW GdMSGHi (B- (3GdhSW (B- (3GdGfMQGa GdeYjGQi h ebjGS HGQjJh(B) (3dJMOjO fSHI (B80:20 (3GdJi JDcO fhYjI GdeTcdGJ GdJi JDKQ HTcd cHjQ Ydi MOhK GdCYWGd h GdJQcjR YdjgG h eMGhdI YdGLgG(B. (3h HGdJGdi Je OQGSI GdhVY GdMGdi ddCYWGd HTcd eaUd ceG SHb h Je GdJCcjO Ydi MOhK GdeTGcd h Je JMOjO fhYjI GdCYWGd GdCcKQ JcQGQ h JCKjQG(B. (3h dCf YedjI GdJMSjf GdeSJeQ gi YedjI YdejI dgG fXQjGJ eNJdaI h dgG WQb cKjQI dJaYjdgG abO Je YQV eaghe YedjGJ GdJMSjf GdeSJeQ HTcd YGe h Je YQV eLehYI GdfXQjGJ GdJi JMOKJ Yf YedjI GdJMSjf GdeSJeQ h GdWQb GdeNJdaI dJWHjb Jdc GdfXQjGJ s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddHMhK GdCMUGFjI (B- (3bSe GdOQGSGJ GdegfjI ai GdVHW GdCMUGFi h JhcjO GdLhOIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdLhOIs; (3GdUjGfIs; (3Gdfbds